Associação entre o torque abdutor do quadril e dos torques flexor e extensor do joelho com o momento externo abdutor do joelho durante o side-step cutting - Bianquini, Vinícius (Universidade Federal de São Carlos, 2025)
Most anterior cruciate ligament (ACL) injuries in sports result from non-contact mechanisms, occurring during activities that involve jump landing, deceleration, and/or changes of direction. The external knee abduction moment is a predictor of primary ACL injury in female athletes. Side-step cutting is a common task in sports involving deceleration and change of direction. Previous research has indicated a high external knee abduction moment during side-step cutting. Although some studies have identified predictors of external knee abduction moment during side-step cutting, little is known regarding the association between hip and knee muscle strength and the external knee abduction moment in healthy female athletes performing this task. Therefore, the aim of this study was to investigate whether there is an association between isometric hip abductor torque, knee flexor and extensor torque, and the knee flexor/extensor torque ratio with the external knee abduction moment during 45° side-step cutting. Twenty-one healthy female athletes (21.8±2.65 years) participated in this study. Isometric hip abductor torque and knee flexor and extensor torque were measured using handheld dynamometry. The external knee abduction moment during side-step cutting was calculated through inverse dynamics procedures. The hip and knee torque, as well as the external knee abduction moment were normalized by each participant's body weight and height. The association between torque measures and the external knee abduction moment was evaluated using a quadratic rank generalization of Spearman's rho squared (ρ2) with a statistical significance level set at 5%. No association was found between hip abductor torque (ρ2 = 0,16; p = 0,204), knee flexor torque (ρ2= 0,04; p = 0,672), knee extensor torque (ρ2= 0,20; p = 0,130), and the knee flexor/extensor torque ratio (ρ2 = 0,08; p = 0,459) with the external knee abduction moment. Thus, in healthy female athletes, the isometric hip abductor torque, knee flexor and extensor torque, and the knee flexor/extensor torque ratio, assessed by handheld dynamometry, are not associated with the external knee abduction moment during 45° side-step cutting.
Association between hip abductor torque and knee flexor and extensor torques with external knee abduction moment during side-step cutting
Keywords: Ligamento cruzado anterior; Lesão; Biomecânica; Cinética; Anterior cruciate ligament; Injury; Biomechanics; Kinetics; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL